Issues in security management : thinking critically about security - Robinson, Robert R., 1922- (Boston : Butterworth-Heinemann, 1999)
This book went beyondg workaday applications and routines to an understanding of the the social significance of careers in security.
Includes bibliographical references.
rua 06/03/15
Loans
Keywords: Private security services -- Canada; Crime prevention -- Canada; Crime prevention; Private security services